Kajian Hukum Penyelesaian Perkara Perdata Melalui Gugatan Sederhana Berbasis E-Court di Pengadilan Negeri Sidenreng Rappang - Herul Herul; Sunardi Purwanda; Muhammad Sabir Rahman; Bakhtiar Tijjang; Aksah Kasim (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine and analyze the implementation of civil case resolution via E-Court-based small claims procedures at the District Court, the factors hindering the implementation of electronic small claims at the Sidrap District Court, and the obstacles encountered in this process. The study employs a normative-empirical research design, utilizing both statutory and socio-legal approaches. Data sources include both primary and secondary data. Data analysis is conducted through observational-sensory and theoretical-rational methods, employing a reasoning model that proceeds from inductive logic to deductive logic. The study finds that the implementation of civil case resolution via E-Court-based small claims at the District Court is governed by Supreme Court Regulation No. 4 of 2019 (amending Supreme Court Regulation No. 2 of 2015 on Small Claims Resolution Procedures) and Supreme Court Regulation No. 7 of 2022 (on Electronic Case Administration and Court Proceedings). The process comprises the following stages: registration (E-Filing), payment (E-Payment), review of claim completeness, appointment of the presiding judge and substitute clerk, summoning of parties (E-Summons), conciliation, trial proceedings (E-Litigation), and the rendering of the judgment. In the E-Court system, judges upload official copies of rulings—electronically signed using digital certificates (e-sign) from the Electronic Certification Center (BSrE)—into the SIPP and E-Court systems. Factors hindering the implementation of electronic-based small claims lawsuits at the Sidrap District Court, as well as obstacles in resolving such civil cases, include: administrative factors (errors in uploading or transmitting files/documents, identity verification issues, problems with advance court fees, administrative errors in summoning parties, and delays in sending hearing documents); public factors (legal understanding and culture, where the public lacks knowledge regarding E-Court and still views face-to-face court services as necessary); and infrastructure factors (issues with internet networks and the E-Court system/application). Additionally, regulatory obstacles exist regarding Supreme Court rules on E-Court and small claims; these regulations address procedural aspects but fail to provide mechanisms for resolving issues that arise during the actual implementation of electronic-based small claims proceedings.